Pidana Seumur Hidup Dalam Sistem Pemasyarakatan - Maulani, Diah Gustiniati (JURNAL PREAVIA, 2011)
The research is to study about longlive prison affairs in the society sistem. the research uses normtive judication. The result of research indicates that the policy of longlife person affairs with using a society system is not suitable and does not reach the criminal purpose. As country based on pancasila foundation, the policy of law must use pancasila foundation.